Educational Props Development for Primary School and Early Childhood Education Teachers: Teachers Satisfaction Aspect - Mujtahid, Iqbal Miftakhul; Berlian, Mery; Vebrianto, Rian; Thahir, Musa (Universitas Pendidikan Ganesha, 2021)
To maintain the continuity of science education through practicum/experimental activities, teachers have several problems in developing alternative simple science teaching aids which are easier and more affordable to provide and simple to use because they do not break easily. This study aims to analyze the level of satisfaction of the Community Service Program based on the problems faced by Elementary School and Early Childhood Education Teachers. This research is a cross-sectional study using a satisfaction survey of the assistance that has been carried out. The research subjects involved in this study were 30 participants who would be assessed in this study. The results showed that the Community Service Program succeeded in overcoming the problems faced by Elementary School and Early Childhood Education Teachers. This is evidenced by the high participation of teachers in participating in training and the success of teachers in developing educational teaching aids. This research has clear implications in developing innovative alternative media in the field of science.